The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/4681989
|View full text |Cite
|
Sign up to set email alerts
|

Management of Giant Gastric Ulcer Perforation: Report of a Case and Review of the Literature

Abstract: Giant gastric ulcer (GGU) is defined as an ulcer more than 3 cm in diameter. Now infrequent in clinical practice, in the pre-H2 receptor antagonist (H2RA) era, the incidence of GGU varied between 12 and 24% of all gastric ulcers. Proton pump inhibitors reportedly achieve better healing rates and symptom relief in comparison to H2RA. The GGU is associated with high incidence of serious complications such as hemorrhage. A perforated GGU though rare (<2%) offers serious challenges in management. We report one suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The choice of approach in the management of gastric perforation, regardless of its size, depends on the infrastructure of the Center and the operator. Indeed, laparoscopy is now increasingly used, even before a giant gastric ulcers [18]. Many authors reported its safety and efficiency in this case [21][22][23].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The choice of approach in the management of gastric perforation, regardless of its size, depends on the infrastructure of the Center and the operator. Indeed, laparoscopy is now increasingly used, even before a giant gastric ulcers [18]. Many authors reported its safety and efficiency in this case [21][22][23].…”
Section: Discussionmentioning
confidence: 81%
“…In our series, the discovery of pneumoperitoneum on radiological images which led us to suspect an hollow organ perforation, was sufficient to decide for an urgent surgery. Furthermore, abdominal ultrasound and Computed Tomography with contrast injection can also help to guide diagnosis by the presence of intra-abdominal fluid effusion but have the disadvantage of being more expensive and depend on the operator In the case of a large gastric ulcer perforation, CT has its advantage because, in addition to the presence of pneumoperitoneum, it could specify the site of perforation by the concentration of extraluminal air bubbles in immediate proximity or by revealing a thickening of the focal wall of the stomach and its discontinuity [18]. Extravasation of the oral contrast on CT gives the diagnosis of perforation with a low sensitivity, between 19% and 42% with the risk of delaying the surgical procedure [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prognosis in elderly patients are particularly poor because of advanced age and comorbidities [14,15]. Furthermore, there is no specific recommendation for their management despite a variety of repair techniques being described [12,16]. Here, we aim to describe a novel technique used to treat such patients, especially those of advanced age, in our institution and to review the current literature.…”
Section: Introductionmentioning
confidence: 99%